2019
DOI: 10.1891/0886-6708.vv-d-18-00075
|View full text |Cite
|
Sign up to set email alerts
|

Dangerous Liaisons: The Role of Hookups and Heavy Episodic Drinking in College Sexual Victimization

Abstract: Heavy episodic drinking (HED) and hookups increase college women's vulnerability to sexual victimization. We examined whether the effect of HED on first year college sexual victimization severity was mediated via hookups, that is, casual sexual encounters between individuals not in a relationship. We also tested the hypothesis that greater sexual limit-setting would attenuate the positive effect of hookups on sexual victimization. Freshman women (N = 335) were recruited by e-mail to complete an online survey r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Similarly, studies have found that individuals who had engaged in risky sexual behavior (e.g., having multiple sexual partners, unprotected sex, and sexually permissive attitudes) were significantly more likely to be sexually victimized (MacGreene & Navarro, 1998;Monks et al, 2010;Testa et al, 2010). The intensity of sexual victimization may be exacerbated by the consumption of alcohol and/or drugs (by the offender or victim, or both) (Corbin et al, 2001;Jaffe et al, 2020;Testa et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies have found that individuals who had engaged in risky sexual behavior (e.g., having multiple sexual partners, unprotected sex, and sexually permissive attitudes) were significantly more likely to be sexually victimized (MacGreene & Navarro, 1998;Monks et al, 2010;Testa et al, 2010). The intensity of sexual victimization may be exacerbated by the consumption of alcohol and/or drugs (by the offender or victim, or both) (Corbin et al, 2001;Jaffe et al, 2020;Testa et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, when researchers attempt to identify the pathway by which alcohol and substance use increase the likelihood of sexual violence victimization, the results are nuanced with mediating variables such as hook-ups (Testa et al, 2019) and number of consensual sexual partners (Franklin, 2010). The relationship between campus parties, alcohol and substance use, hooking up, and sexual assault has also been analyzed at the institutional level, with one study finding that sexual assault is “a predictable outcome” of campus partying culture (Armstrong et al, 2006, p. 483).…”
Section: Discussionmentioning
confidence: 99%
“…They may be increasingly excluded from healthier social groups and gravitate towards others with more chaotic and even antisocial behaviour, placing them in situations where victimisation is more likely. Research has indicated that both heavy‐episodic drinking and greater association with deviant peers are risk factors for victimisation (Litherland et al., 2021; Testa et al., 2019; Vézina et al., 2011; Wojciechowski, 2022). Because alcohol‐related disorders are positively associated with both (Coder et al., 2009; Jenkins et al., 2011; Miranda et al., 2013; Sloan et al., 2011), there is a potential that either or both mediate the relationship between alcohol dependence and victimisation.…”
Section: Introductionmentioning
confidence: 99%